Study on the Life-Cycle Health Monitoring Technology of Water-Rich Loess Tunnel - Xiaohui Xue; Yongli Xie; Xinxing Zhou (Advances in Materials Science and Engineering)
The engineering properties of water-rich loess tunnel will decline sharply because of the existence of water, which threats the safety and stability of the tunnel seriously. In order to ensure the safety and stability of the Qiaoyuan tunnel, the life-cycle health monitoring was measured by the vibrating wire sensor and distributed optical fiber. The contact pressure, shotcrete stress, stress of steel arch rib, and strain states of the secondary liner were evaluated. The results of the life-cycle health monitoring demonstrated that the construction procedure, irrigation, and heavy rainfall significantly affected the mechanics morphology of the support structure. In particular, under the influence of irrigation, the shotcrete stress of the left shoulder had risen to 6.21 MPa from 5.30 MPa. Affordable maximum tensile stress of the right shotcrete is 2.15 MPa, which caused the cracking of primary support structure with a crack width of 3 mm to 8 mm. After irrigation and heavy rainfall, the stress of steel arch rib of the left haunch had risen to 135.7 MPa and 298.7 MPa, respectively. In addition, the strain of secondary liner rose to 1498 με from 1278 με continuously at the right sidewall on section YK9 + 685, presenting that the crack was still developing. It indicates that the vibrating wire sensor and the distributed optical fiber were successful in achieving the life-cycle health monitoring of water-rich loess tunnel. This technique has a significant impact on formulating the maintaining measures and reducing the risk of tunnel.